Dietary Oxidative Distress: A Review of Nutritional Challenges as Models for Poultry, Swine and Fish - Elodie Bacou; Carrie Walk; Sebastien Rider; Gilberto Litta; Estefania Perez-Calvo (MDPI AG, 2021)
The redox system is essential for maintaining cellular homeostasis. When redox homeostasis is disrupted through an increase of reactive oxygen species or a decrease of antioxidants, oxidative distress occurs resulting in multiple tissue and systemic responses and damage. Poultry, swine and fish, raised in commercial conditions, are exposed to different stressors that can affect their productivity. Some dietary stressors can generate oxidative distress and alter the health status and subsequent productive performance of commercial farm animals. For several years, researchers used different dietary stressors to describe the multiple and detrimental effects of oxidative distress in animals. Some of these dietary challenge models, including oxidized fats and oils, exposure to excess heavy metals, soybean meal, protein or amino acids, and feeding diets contaminated with mycotoxins are discussed in this review. A better understanding of the oxidative distress mechanisms associated with dietary stressors allows for improved understanding and evaluation of feed additives as mitigators of oxidative distress.